Slot-based approaches to airport congestion management - Jan Keith Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes slot-based approaches to management of airport congestion, using a model where airlines are asymmetric and internalize airport congestion. Under these circumstances, optimal congestion tolls differ across carriers, and since a slot-sale regime (with its uniform slot price) cannot duplicate this pattern, the equilibrium it generates is inefficient. Flight volumes tend to be too low for large carriers and too high for small carriers. Under a slot-trading regime or a slot auction, however, the existence of a fixed number of slots causes carriers to treat total flight volume (and thus congestion) as fixed, and this difference can lead to an efficient outcome.
Keywords: H23; L50; L93; 330; Flughafen; Verkehrsstau; Slotallokation; Luftverkehr; Straßenbenutzungsgebühr; Theorie